Analysis of Guided Inquiry Laboratory Learning Materials To Improve Students's Scientific Process Skills In Newton's Law of Motion (IPF: Inovasi Pendidikan Fisika, 2020)
Abstract The purpose of this study is to develop guided inquiry laboratory learning materials to improve students' scientific process skills in Newton's Law of Motion. The research used a qualitative descriptive analysis of the results of the validity of the learning materials being developing. The results showed that valid and reliable which included the validity of the syllabus, the lesson plan, the handouts, student worksheets, the cognitive learning achievement test, the learning process implementation of learning process, the observation sheet of scientific process skills on student worksheets, and the student questionnaire. So the learning materials with the guided inquiry laboratory was developed is feasible to implemented in learning for improving students’ scientific process skills in Newton's Law of Motion. Keywords: Validity of learning materials, guided inquiry laboratory, scientific process skills Abstrak Tujuan penelitian ini adalah mengembangkan perangkat pembelajaran guided inquiry laboratory untuk meningkatkan keterampilan proses sains peserta didik pada materi Hukum Newton tentang gerak. Penelitian menggunakan analisis deskriptif kualitatif terhadap hasil validitas perangkat yang dikembangkan. Hasil penelitian menunjukkan bahwa perangkat pembelajaran berkriteria sangat valid serta memiliki reliabilitas sangat baik yang meliputi silabus, Rencana Pelaksanaan Pembelajaran (RPP), handout, Lembar Kerja Peserta Didik (LKPD), tes hasil belajar kognitif, lembar keterlaksanaan proses pembelajaran, lembar pengamatan keterampilan proses sains terhadap Lembar Kerja Peserta Didik, dan angket peserta didik. Sehingga perangkat pembelajaran yang dikembangkan dengan model guided inquiry laboratory dapat diimplementasikan dalam meningkatkan keterampilan proses sains peserta didik pada materi Hukum Newton tentang gerak. Kata Kunci: Kevalidan perangkat pembelajaran, guided inquiry laboratory, keterampilan proses sains